2023
DOI: 10.1083/jcb.202206061
|View full text |Cite
|
Sign up to set email alerts
|

SIR telomere silencing depends on nuclear envelope lipids and modulates sensitivity to a lysolipid

Abstract: The nuclear envelope (NE) is important in maintaining genome organization. The role of lipids in communication between the NE and telomere regulation was investigated, including how changes in lipid composition impact gene expression and overall nuclear architecture. Yeast was treated with the non-metabolizable lysophosphatidylcholine analog edelfosine, known to accumulate at the perinuclear ER. Edelfosine induced NE deformation and disrupted telomere clustering but not anchoring. Additionally, the association… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 187 publications
0
1
0
Order By: Relevance
“…When the nuclear envelope structure is distorted, Sir4 interaction with telomeric regions and subsequent hyperclustering is disrupted, resulting in loss of transcriptional silencing. A recent study investigated the impact of Sir4/telomere interaction disruption and found that ribosomal protein gene expression was notably downregulated due to accumulative rDNA compaction 49 . The telomeric silencing by Sir proteins is shown to be dependent on nuclear envelope lipid content, where links between chromatin remodeling and lipid metabolism have been previously established.…”
Section: Sir In Subtelomeric Gene Silencingmentioning
confidence: 99%
See 1 more Smart Citation
“…When the nuclear envelope structure is distorted, Sir4 interaction with telomeric regions and subsequent hyperclustering is disrupted, resulting in loss of transcriptional silencing. A recent study investigated the impact of Sir4/telomere interaction disruption and found that ribosomal protein gene expression was notably downregulated due to accumulative rDNA compaction 49 . The telomeric silencing by Sir proteins is shown to be dependent on nuclear envelope lipid content, where links between chromatin remodeling and lipid metabolism have been previously established.…”
Section: Sir In Subtelomeric Gene Silencingmentioning
confidence: 99%
“…The telomeric silencing by Sir proteins is shown to be dependent on nuclear envelope lipid content, where links between chromatin remodeling and lipid metabolism have been previously established. Modification of the nuclear envelope altered telomeric SIR clustering and resulted in a partial loss of complex silencing at subtelomeric genes 49 .…”
Section: Sir In Subtelomeric Gene Silencingmentioning
confidence: 99%
“…Homeoviscous adaptation (HA) is the most well-known strategy. 50–66 In HA, depending on the temperature the saturated to unsaturated lipid ratio changes. With decreasing temperature, some of the lipids with saturated fatty acid tails are converted to unsaturated lipids with the help of desaturase enzymes.…”
Section: Introductionmentioning
confidence: 99%